IMPROVING THE LIFE KNOWLEDGE OF STUDENTS IN UZBEKISTAN ACCORDING TO THE INTERNATIONAL ASSESSMENT OF NATURAL LITERACY SCIENCES PISA (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This thesis is about "Assessment of educational achievements of students in natural science based on TIMSS tasks" and provides insights into the essence of natural science and PISA research.